Postoperative Thirst in Surgical Patients: A Bibliometric Study - Ozsoy, Hatice; Cankaya, Askeri; Ozkan, Esra; van Giersbergen, Meryem Yavuz (Elsevier Science Inc, 2025)
Purpose: Thirst during surgical intervention is an important parameter that may affect the clinical course of patients. In this context, although there is a large body of knowledge in the existing literature on thirst during the surgical period, the lack of bibliometric analysis on this subject is striking. This study aims to systematically evaluate scientific publications on thirst during the surgical period, to fill the gaps in the literature, and to provide new perspectives that can guide clinical practice. Design: Descriptive and bibliometric analyses were used. Methods: The study universe consisted of 256 articles on postoperative thirst in the SCOPUS database. The study data were analyzed with Excel and they were visualized with VOSviewer and Bibliometrix Package in R software. Findings: In the study, it was determined that the 256 articles identified were published in 181 different sources between 1969 and 2024, with a total of 1,194 authors contributing to these articles. In this research area, the top 3 publishing countries, China (111) has the highest productivity, followed by the United States (67) and Brazil (52). Most of the articles were published in Journal of Perianesthesia Nursing, British Journal of Anesthesia, and Acta Anaesthesiologica Scandinavica. Conclusions: The year and forecast analysis show that the number of studies on thirst, which is an important problem among surgical patients, has increased and will increase in the coming years. The increasing interest in thirst as an important problem among surgical patients shows that the interest and demand for research in this field are increasing. (c) 2025 American Society of PeriAnesthesia Nurses. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: bibliometrics; patient; postoperative period; surgery; thirst